Is Corporate Social Responsibility Able to Mediate Increased Tax Avoidance? - Kiryanto; Alfiana Rohmatika; Farikha Amilahaq (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of the variable profitability, company growth and institutional ownership structure on tax avoidance through corporate social responsibility. The sample used in this research is financial reports of manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2016-2019, while the method in this study uses purposive sampling with a total of 32 samples of manufacturing companies. The analysis technique used is WarpPLS version 5.0. The results indicate that profitability and company growth have a positive and significant effect on corporate social responsibility, but institutional ownership structure has a negative insignificant effect on corporate social responsibility. Profitability has negative and significant impact toward tax avoidance, while company growth and institutional ownership structure has no significant impact toward tax avoidance. As for corporate social responsibility has negative and significant impact toward tax avoidance, and it could be intervening variable between company growth and tax avoidance.  The research has implications for policy makers in this case the government that CSR is able to reduce tax avoidance. Therefore, the government always encourages companies to carry out CSR in order to reduce tax avoidance in the hope that tax revenues can increase.